On the arbitrariness of consumption - John Whalley; Shunming Zhang (Center for Economic Studies and ifo Institute (CESifo), 2009)
We discuss a simple model of choices of joint consumption by a working couple who place maintenance of their marriage (relationship) above all else. Any proposal made by one partner seeking to provide maximal utility to the other so as to preserve the marriage, in the case where preferences of partners are unknown, will be accepted. In this sense consumption is arbitrary. In a concluding section we suggest that while overly simple; this structure may characterize to some degree significant amounts of observed consumption, emphasing how social arrangements and the value placed on them by individuals can impact on observed economic behaviour.
Keywords: A10; A12; A13; C50; D01; 330; Values; Preferences; lexicographic; relationship; partners; Konsumtheorie; Ehe; Haushaltsökonomik; Konsuminterdependenz; Soziale Werte; Theorie